Pembiasaan Shalat Dhuha Dalam Membentuk Karakter Siswa Di MTs An-Nur Pamekasan - Rofiatul Hosna; Adibah, Adibah; Suharto, Royyanatul Mahbubah (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study examines the implementation of character education through the habit of Dhuha Prayer at MTs An-Nur Pamekasan. Character education plays an important role in shaping the nation's character and civilization, which is in line with the goal of national education, which is to educate the nation's life. Data was collected through observation, interviews, and documentation. Data is obtained through qualitative descriptive analysis by reducing data, presenting data to drawing data conclusions. Furthermore, the validity of the data was checked through triangulation techniques and using reference materials. The findings of the research are that the habit of Dhuha Prayer can provide character education value to students, create a school environment oriented to character development, students are also familiar with religious matters, discipline in any matter and responsible. And also several supporting factors in the form of teacher and parent motivation, student awareness and enthusiasm, as well as adequate facilities and infrastructure. There are also inhibiting factors, namely lack of time availability, lack of discipline and involving the family background of students who still have a minimal understanding of Islamic religious science.